Managing social comparison costs in organizations - Óscar F. Contreras; Giorgio Zanarone (Banco de México, 2018)
This paper studies how organizations manage the social comparisons that arise when their employees' pay and tasks, and hence their status vis-à-vis peers, differ. We show that under a "pay transparency policy", the organization may compress pay and distort the employees' tasks to minimize social comparison costs. We subsequently show that if the organization can credibly commit to informal agreements, it may remove social comparisons by implementing a "pay secrecy" policy. Under such a policy, the organization makes employees "officially equal" by granting them similar formal terms, while optimally differentiating their pay through self-enforcing informal adjustments.
Keywords: D03; D23; M52; M54; 330; Social Comparisons; Organization Design; Informal Contracts; Formal Contracts